Circular economy: the pedagogical case study of Corticeira Amorim’s business model - Folhas, Maria Inês Rodrigues (2020)
In a world that is increasingly facing its physical limits, it is necessary to find alternatives for a more sustainable consumption of resources. Circular Economy (CE) is presented as a new model of resource use, contrary to the linear economy model that still prevails. Nowadays, businesses have started to explore new ways to rethink their business models by reusing their products, decreasing their resources and retaining their value for longer and more efficiently. This Pedagogical Case Study is based on the Circular Economy model applied in Corticeira Amorim, one of the largest Portuguese companies that has been present in the cork sector for 150 years. This case study aims to analyse how Corticeira Amorim applies the CE model throughout its production cycle, and whether the application of this model presents benefits for the company, environment and society. The case study focuses firstly on the description of the company and, in order to answer the questions and objectives, a specialized literature review on the subject was performed, where it was described the historical evolution of the model, the schools of thought that support CE, its principles and the changes that it brought to the business models. The results demonstrated through the development of the proposed questions indicate that Corticeira Amorim applies the principles of Circular Economy throughout its production cycle, from the extraction of the cork until the waste generated and that the use of a sustainable policy and compliance with CE principles are beneficial for the environment, society, and company.